2021
DOI: 10.47278/journal.abr/2020.023
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Ecological Adaptations of Blackbuck (Antilope Cervicapra): A Review

Abstract: Blackbuck is the existing members of genus Antilope which is most elegant and graceful among all Antelopes of Asia with distinct sexual dimorphism. Blackbuck show endemism in Pakistan, Nepal and India occupying mainly the semi-arid grassland areas. The name of species attributes towards the dark brownish to blackish coat color of male species. While female and the young ones are tawny or yellow. Chin undersides of legs and chest are white in both male and female individuals. Males have whorled horns with 79cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Listeria monocytogenesis the main bacteria that bear on the species (krüger 1963;Webb and rebar 1987). Protozoas like Trypanosoma cruzi has also impacted over the population of Blackbuck species (Schmidt et al 1981;Tahir et al 2021 Fracture is a leading cause of death in free-ranging ruminants when it comes to non-infectious diseases. Tibial fracture is the most common long bone fracture in small ruminants.…”
Section: Habitatmentioning
confidence: 99%
See 4 more Smart Citations
“…Listeria monocytogenesis the main bacteria that bear on the species (krüger 1963;Webb and rebar 1987). Protozoas like Trypanosoma cruzi has also impacted over the population of Blackbuck species (Schmidt et al 1981;Tahir et al 2021 Fracture is a leading cause of death in free-ranging ruminants when it comes to non-infectious diseases. Tibial fracture is the most common long bone fracture in small ruminants.…”
Section: Habitatmentioning
confidence: 99%
“…Treatment of traumatic injuries in non-domestic animals is also difficult because to difficulties in restraint and wound dressing. Antibiotic sensitivity test showed that ciprofloxacin had the highest sensitivity, followed by amoxicillin + Salabactam, amoxycillin, amoxicillin and cefotaxime (kumari et al 2017;Singh et al 2019;Tahir et al 2021).…”
Section: Habitatmentioning
confidence: 99%
See 3 more Smart Citations